Adult‐onset Still's disease in Western Australia: Epidemiology, comorbidity and long‐term outcome. (24th August 2022) - Nossent, Johannes; Raymond, Warren; Keen, Helen; Preen, David B.; Inderjeeth, Charles A.
Abstract: Aim: Adult‐onset Still's disease (ASD) is a rare, potentially life‐threatening autoinflammatory condition. As reported prevalence shows regional variation and long‐term outcome data are scarce, we investigated epidemiology and long‐term health outcomes of ASD in Western Australia (WA). Methods: Population‐based cohort study using longitudinally linked administrative health data from all WA hospitals between 1999 and 2013 for ASD patients (ICD‐10‐AM M06.1) and controls matched for age, gender, and index year. Rate ratios and odds ratios (RR/OR) with 95% confidence intervals (CI) compared ASD patients with controls. Results: The average ASD incidence (n = 52) was 0.22/100 000 with 2.4/100 000 point‐prevalence as of December 31, 2013. ASD patients (median age 41.5 years, 59.6% female) had higher odds of previous liver disease (OR 2.67, 95% CI 1.31‐5.45), fever (OR 54.10, 95% CI 6.60‐433.0), rash (OR 15.70, 95% CI 4.08‐60.80), and serious infections (OR 4.36, 95% CI 2.11‐22.80) than controls. Despite biological disease‐modifying antirheumatic drugs in 27% of patients, ASD patients had higher odds for joint replacement (n = 7, 13.5%) (OR 45.5, 95% CI 4.57‐93.70), osteoporosis (OR 31.3, 95% CI 3.43‐97), and serious infections (RR 5.68; 95% CI 6.61‐8.74) during follow up. However, crude mortality (11.5% vs 7.5%; P = 0.34), survival at 1 and 5 years ( P = 0.78), and last modified Charlson Comorbidity score (median 2 vs 2) were similar between groups. Conclusion: The epidemiology and demographics of ASD in Western Australia fall within the internationally reported range. ASD patients present increased rates of liver disease, rash, and serious infections before disease onset. Mortality following ASD was not increased for 5 years despite high rates of chronic arthritis requiring joint replacement, serious infections, and osteoporosis.